A Brief History of GeoPangea Research Group - Agung Budiman; Iqbal Fardiansyah; Leon Taufani (Ikatan Ahli Geologi Indonesia, 2013)
GeoPangea Research Group (GPRG) is an independent research group founded on May 31st, 2010, led by ideas from young and passionate geology students of UPN ”Veteran” Yogyakarta. The group is supervised by Dr. C. Prasetyadi, a faculty member of the Geology Department, as well as a mentor to all research-related activities conducted by GPRG. This group aims to contribute to scientific knowledge in numerous aspects of geosciences (i.e. regional geology, sedimentology and stratigraphy, structural geology, tectonics, etc.) by performing research and demonstrating their application in hydrocarbon exploration. The results of our research are documented as published papers and articles in various journals and scientific conferences of both regional and international levels.